Lung transplantation for high-risk patients with idiopathic pulmonary fibrosis - De Oliveira, Nilto C; Julliard, Walker; Osaki, Satoru; Maloney, James D; Cornwell, Richard D; Sonetti, David A; Meyer, Keith C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Survival for patients with idiopathic pulmonary fibrosis (IPF) and high lung allocation score (LAS) values may be significantly reduced in comparison to those with lower LAS values. Objectives: To evaluate outcomes for high-risk IPF patients as defined by LAS values ≥46 (N=42) versus recipients with LAS values